1992
DOI: 10.1007/bf00598962
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the adjustable pressure ventricular valve in magnetic resonance imaging: problems and solutions

Abstract: We performed magnetic resonance imaging in 30 patients with hydrocephalus with Sophy adjustable pressure valves (PAVS). A pressure check following the MRI study showed a significant proportion with pressure valve changes, which could easily be readjusted by percutaneous manipulation. The value of the PAVS and its safety during MRI examinations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…It is also noteworthy that there are in vivo counterforces for certain implants that prevent these devices from presenting a hazard to patients in association with the MRI environment [25,31]. Since 1985, percutaneously adjustable CSF shunt valves have been used [27,28], but the possibility that toy magnets and the use of MRI in patients with adjustable valves might affect the adjustment mechanism has been underestimated [45,46]. In our study 50 % of the tested Codman-Medos magnetically adjustable CSF shunt valves showed a loss of adjustability after exposure to a 3.0-T static magnetic field (• ▶ Table 6).…”
mentioning
confidence: 99%
“…It is also noteworthy that there are in vivo counterforces for certain implants that prevent these devices from presenting a hazard to patients in association with the MRI environment [25,31]. Since 1985, percutaneously adjustable CSF shunt valves have been used [27,28], but the possibility that toy magnets and the use of MRI in patients with adjustable valves might affect the adjustment mechanism has been underestimated [45,46]. In our study 50 % of the tested Codman-Medos magnetically adjustable CSF shunt valves showed a loss of adjustability after exposure to a 3.0-T static magnetic field (• ▶ Table 6).…”
mentioning
confidence: 99%
“…Accidental resetting of the shunt opening pressure by the strong magnetic field of the magnetic resonance imager has been a problem for most pressure programmable devices. 7,13) Moreover, daily life commonly involves exposure to a wide variety of magnetic devices or fields. This special feature of the DSV gives a great sense of inner security to the patients, as well as the medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pressure setting may be accidentally changed by the effect of powerful external magnetic fields, such as those used by magnetic resonance imaging. 3,6,8) Pressure settings are reportedly also affected by weak magnetic fields associated with everyday objects, such as telephone loudspeakers, headphones, hairdryers, a magnetic pillow, and even a toy containing a magnet. 1,8,10) We present the case of a 7-year-old girl who tended to touch a television with her head during play, resulting in a change in the programmable valve pressure.…”
Section: Introductionmentioning
confidence: 99%